Southeast Asians and the Asia-Europe Meeting (ASEM): : State's Interests and Institution's Longevity - Fitriani, Evi (Book collections on Project MUSE., 2014)
The inauguration of the Asia-Europe Meeting (ASEM) in Bangkok in 1996 was celebrated with enthusiasm and hopes in the two regions because this forum represented a breakthrough in Asia-Europe relations. The region-to-region pattern of the relations becomes the study framework that enables the explorations of central themes which include the Asian regional identity, ASEAN collective diplomatic prominence, and the informality of the ASEM institution. In exploring those central themes, this boo ...